Excellent hardening effect in lead-free piezoceramics by embedding local Cu-doped defect dipoles in phase boundary engineering - Xinyue Qiu; Chao Wu; Daniel Q. Tan; Ruihong Liang; Chen Liu; Yinchang Ma; Xi-xiang Zhang; Shiyang Wei; Junwei Zhang; Zhi Tan; Zhipeng Wang; Xiang Lv; et al. (Nature Communications)
Abstract Piezoceramics for high-power applications require both high piezoelectric coefficient (d 33) and mechanical quality factor (Q m). However, the trade-off between them poses a significant challenge in achieving high values simultaneously, which is more prominent in lead-free piezoceramics. Here, we propose a new strategy, local Cu-acceptor defect dipoles embedded orthorhombic-tetragonal phase boundary engineering (O-T PBE), to balance d 33 and Q m in potassium sodium niobate piezoceramics. This is validated in 0.95(K0.48Na0.52)NbO3-0.05(Bi0.5Na0.5)HfO3-0.2%molFe2O3-xmol%CuO ceramics. Our strategy simultaneously maintains the O-T PBE and introduces local dimeric $${(Cu_{Nb}^{{′} {′} {′} }-V_{O}^{\bullet \bullet })}^{{′} }$$ ( C u N b ″ ′ − V O ∙ ∙ ) ′ and trimeric $${\left(V_{O}^{\bullet \bullet }-Cu_{Nb}^{{′} {′} {′} }-V_{O}^{\bullet \bullet }\right)}^{\bullet }$$ V O ∙ ∙ − C u N b ″ ′ − V O ∙ ∙ ∙ defects. The dimeric defects form defect dipole polarization that pins domain wall motion, while the trimeric ones introduce the local structural heterogeneity that leads to nano-scale multi-phase coexistence and abundant nano-domains. Encouragingly, for the Cu-doped sample with x = 1, Q m increases by a factor of 4, but d 33 only decreases by 1/5 (i.e., achieving a d 33 of 340 pC/N and a Q m of 256). Our research provides a new paradigm for balancing d 33 and Q m in lead-free piezoceramics, which holds promise for high-power applications.